APC Injuries With Symphyseal Fixation: What Affects Outcome?. Issue 1 (January 2017) - Lybrand, Kyle; Bell, Anthony; Rodericks, Deirdre; Templeman, David; Tornetta, Paul
Abstract : Objective: To evaluate the influence of the symphyseal position at union, implant failure, and the type of posterior ring injury on validated outcome measures. Design: Retrospective review with prospectively collected validated outcome data. Setting: Two academic level 1 trauma centers. Patients/Participants: We evaluated 54 patients with operatively treated anterior-posterior compression (APC) type 2 and 3 injuries. Intervention: Thirty-five APC type 2 and 19 APC type 3 injuries were reviewed at a minimum of 2 years after surgery. Average follow-up was 7 years. Main Outcome Measures: Patients were evaluated with validated EuroQol five dimensions (EQ5D), EuroQol health index, Visual Analog Score (VAS) pain, Majeed pelvic scores, and change in work status. The final anterior-posterior (AP) radiograph available was reviewed for implant failure and displacement. Revision surgery was documented based on implant status and displacement at final follow-up. Results: There were trends toward better outcomes for APC type 2 for EQ5D and VAS pain. Patients with injury severity score (ISS) >16 had worse reported health, Majeed scores, and VAS pain. Nineteen patients had failure of fixation. There were no differences in any outcome measure; trends toward better Majeed score were found for patients with intact fixation. Displacements >15 mm anteriorly at final follow-up negatively affect outcomes with significantly worse EQ5D, reported health, and Majeed score. Two patients required revision surgery. There were no differences in final outcomes. Conclusions: No significant differences were found for APC type 2 versus type 3 injuries. Higher injury severity score resulted in worse outcomes and more pain. Outcomes were not effected by implant failure; however, major loss of reduction (>15 mm) anteriorly did negatively impact outcomes. Patients with failure who were revised to union did not have worse outcomes. Level of Evidence: Prognostic level IV. See Instructions for Authors for a complete description of levels of evidence.